Low Bioactive Vitamin D Is Associated with Pregnancy-Induced Hypertension in a Cohort of Pregnant HIV-Infected Women Sampled Over a 23-Year Period - Van Winden, Kristi R.; Bearden, Allison; Kono, Naoko; Frederick, Toni; Operskalski, Eva; Stek, Alice; Pandian, Raj; Barton, Lorayne; Kovacs, Andrea (American Journal of Perinatology, 2019)
Objective To examine the association of vitamin D insufficiency and risk of pregnancy-induced hypertension (PIH) among human immunodeficiency virus (HIV)-infected pregnant women.Study Design This is a retrospective cohort study evaluating the impact of low maternal vitamin D levels on PIH and perinatal outcomes among HIV-infected pregnant women receiving care at an urban HIV center from 1991 to 2014.Results A total of 366 pregnant women were included, of which 11% developed PIH. Lower levels of 25-hydroxyvitamin D (25(OH)D) and bioactive 1,25-dihydroxyvitamin D (1,25(OH)2D) were associated with increased HIV disease activity. 25(OH)D levels were not significantly associated with the incidence of PIH. Higher 1,25(OH)2D levels were associated with reduced incidence of PIH in univariate (odds ratio, OR: 0.87 [95% confidence interval, CI: 0.79–0.95], p = 0.004) and multivariate (OR: 0.88 [95% CI: 0.80–0.97], p = 0.010) analyses. No association was found between 25(OH)D levels and other obstetric outcomes. Lower 1,25(OH)2D levels were associated with group B Streptococcus colonization (OR: 0.92 [95% CI: 0.86–0.99]) and low birth weight (LBW) (OR: 0.90 [95% CI: 0.83–0.98]) on multivariate analysis. Mean 1,25(OH)2D levels were significantly lower in women with preterm delivery and LBW infants.Conclusion Lower bioactive vitamin D levels are related to PIH in HIV-infected women. This association may be related to the coexistence of abnormal placental vitamin D metabolism and abnormal placental implantation.
Keywords: pregnancy; hypertension; preeclampsia; pregnancy-induced hypertension; vitamin D; human immunodeficiency virus